Pharmacological characterization of geraniol in sheep and its potential use in the control of gastrointestinal nematodes - Miró, María Victoria (2022)
Geraniol (GNL) was effective against gastrointestinal nematodes in vitro; nevertheless, the anthelmintic effect of phytochemicals combined with synthetic drugs has been little explored in vivo. This article characterized in vitro / in vivo the pharmacological features of GNL in sheep as well as its pharmacokinetic interaction with albendazole (ABZ). Additionally, the in vivo efficacy of GNL against Haemonchus contortus was evaluated in lambs. Liver microsomes from lambs were incubated in the absence or presence of GNL to analyze CYP1A1, CYP1A2 and FMO metabolic pathways. The effect of GNL on the hepatic sulfoxidation and sulfonation of ABZ and the ruminal sulforeduction of albendazole sulfoxide (ABZSO) was assessed. The in vivo pharmacokinetic interaction of ABZ and GNL was evaluated in lambs. The effect of GNL on the fecal egg count was evaluated in lambs infected with a resistant isolate of H. contortus. In sheep liver microsomes, the presence of 2 mM GNL reduced the CYP1A1, CYP1A2 and FMO pathways by 77.9, 90.8 and 84.5%, respectively, with respect to control (P < 0.05). In the presence of 2 mM GNL, the ABZ sulfoxidation decreased from 114.4 ± 8.49 (control) to 50.24 ± 11.1 nmol/min.mg, and ABZSO2 production decrease from 0.52 ± 0.14 to 0.09 ± 0.03 nmol/h.mg. No changes in the pharmacokinetic behavior of ABZ were observed in the presence of GNL. The in vivo efficacy of four doses of GNL was 40.5%. These findings highlight the importance of integrated in vitro / in vivo pharmaco-parasitological studies to develop new pharmacological tools for controlling gastrointestinal parasites.